Revitalizing Local Culture in Nusantara Music - Putra, Irdhan Epria Darma; Wimbrayardi, Wimbrayardi; Ferdian, Robby (Universitas Negeri Medan, 2023)
Revitalization is a systemic process and methodology to reactivate local potentials in the context of preserving important cultures in the face of changing times. Revitalization of local culture as a big job, not just an activity to explore the heritage of tradition and then preserve it. Rather, that local culture stored in cultural heritage is used as a light in accompanying and coloring the musical character of the nation. Change can only be through real activities and not discourse,